Determining the Roots Equation of Characteristics - Sri Rejeki Dwi Putranti; Suroso Ari Purnomo (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Characteristic equation an matrix roots called characteristic roots. Here is discussed how to determine the roots of the characteristic of several kind if matrices. Such us Matrix Hermitian, Orthogonal Real Matrix and Matrix Similar.The roots of a Hermition matrix and the characteristic roots of a real symmetric matrix must be real. While the roots of an Orthogonal Riel matrix have 1 as mode. For a Similar matrix, the characteristic roots are the same. Keywords: matrix; root equation; characteristic